Raffinose and Hexose Sugar Content During Germination Are Related to Infrared Thermal Fingerprints of Primed Onion (Allium cepa L.) Seeds - Thakur, Meenakshi; Sharma, Poornima; Anand, Anjali; Pandita, Vinod Kumar; Bhatia, Arti; Pushkar, Suchitra (Frontiers in Plant Science, 2020)
Priming is used to increase vigor, germination synchronization, seedling growth and field establishment by advancing metabolic processes within seeds. Seed respiration is a good indicator of the metabolic processes that lead to transition towards germination. Onion seeds (cv.Pusa Ridhi) subjected to osmopriming (-1.5 MPa PEG6000 for 7 days), magnetopriming (100 mT for 30 min) and halopriming (150 mM KNO3 for 6 days), were evaluated at different times of imbibition to study the emergence index and respiration indices such as infrared thermal fingerprint, CO2 evolution rate, cytochrome c oxidase activity and soluble sugars profile. Haloprimed seeds exhibited 42.5% higher emergence index as compared to unprimed control. Primed and unprimed seeds showed negative values for relative temperature (∆T) (difference in temperature of seed and its immediate environment). Haloprimed seeds had the lowest values (-4.1 to -2.3ºC) compared to other priming treatments over the germination period. Soluble sugars like raffinose, sucrose, glucose and fructose contents were monitored and it was observed that en masse raffinose, glucose and fructose levels were (17.5-59.9%) lower in haloprimed seeds over control. A positive correlation (r2=0.504**) was derived between the amount of these sugars and ∆T. Seed respiration, measured as CO2 evolution rate was more for haloprimed seeds that indicated that these soluble sugars were used as respiratory substrates. Significantly higher cytochrome c oxidase activity (40.7-89.8 and 12.5-66.6%) was observed in all primed seeds at 28 and 36 h, respectively. Among the various seed priming methods, halopriming proved to be the most effective priming treatment in onion seeds as evidenced by the higher respiration indices that resulted in faster metabolic rate and emergence index.